Acute abdominal pictures in acute leukemias - Farcic, Antonio; De Bellis, Roberto; Klempert, Haydée (Cirugía del Uruguay, 1979)
5 patients sufiering from acute l'eukemias presented acute abdominal symptoms and were treated in various medical centres. Within the last few years treatment of acute malignant hemopathies has increased survival considerably. An analysis of the increasing frequency of these complications, of their etiopathogenesis and hystopathology would seem to indicate that, at the present moment, earlier surgery is advisable in the hope of improving their implicit and ominous prognosis.